2012
DOI: 10.3390/w4020321
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Study of the Treatability of Synthetic Stormwater Under Varying Conditions Using Electric Arc Furnace Steel Slag

Abstract: Abstract:The investigation of electric arc furnace (EAF) steel slag as a viable add-on technology to existing stormwater systems for the removal of dissolved phosphorus (P) was extended to explore the effects of varying environmental and treatment system conditions. Parameters such as stormwater composition, P concentration, metal concentration, pH, temperature, slag mass and slag particle size were varied. Observations relating to the method of P removal via EAF slag were also carefully considered to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
2
4
0
1
Order By: Relevance
“…Hence, smaller size of slag has a larger surface area resulting higher adsorption on phosphorus and its removal percentage. These results agreed with the finding in other study [9]. Since the diffusion path decreased as the size of slag decreased, eventually it increased the effectiveness of the penetration of adsorbate as well as then depth of penetration in adsorbent particle resulting higher rate of adsorption.…”
Section: Adsorption Isothermsupporting
confidence: 82%
See 2 more Smart Citations
“…Hence, smaller size of slag has a larger surface area resulting higher adsorption on phosphorus and its removal percentage. These results agreed with the finding in other study [9]. Since the diffusion path decreased as the size of slag decreased, eventually it increased the effectiveness of the penetration of adsorbate as well as then depth of penetration in adsorbent particle resulting higher rate of adsorption.…”
Section: Adsorption Isothermsupporting
confidence: 82%
“…Besides that, the results demonstrated the amount of P adsorbed at pH 3.0 was the greatest which indicated the adsorption of P by EAFS is effective under acidic environment. Although these findings are likely support with several studies but in terms of the optimum value of pH, the value is not similar where their studies indicated pH 5 -5.5 consisted of highest P-removal efficiency [8,9]. Due to the variation of chemical composition in the EAFS hence the optimum pH for highest P-removal efficiency is subjected to the chemical composition.…”
Section: Effects Of Phsupporting
confidence: 55%
See 1 more Smart Citation
“…In the case of the remaining materials, precipitation of Zn and Cu was less significant, because pH was within 5.26 to 7.55 for activated carbon, 5.07 to 7.52 for halloysite, 5.08 to 6.56 for zeolite, and 5.05 to 6.95 for diatomite. Removal of heavy metals on zeolite is generally via ion exchange [36], but also takes place through electrostatic adsorption to negatively charged sites on the zeolite surface [31]. Moreover, heavy metals are removed on halloysite and diatomite via ion exchange and surface complexation respectively on permanently charged sites and variably charged sites [40,60].…”
Section: Equilibrium Testsmentioning
confidence: 99%
“…In the last decade, aside from infiltration systems (filter strips, soakaways, infiltration trenches, infiltration basins) and significantly influence the daily, monthly and annual variability of the removal efficiency of transported contaminants. Most reports are focused on the analysis of the intensity of contaminant removal at ambient temperatures [30][31][32][33] or on assessing the impact of temperature increases above room temperature on the intensification of the process [34][35][36][37]; fewer studies indicate how temperature decrease, even to 0 °C, influences the ability of reactive materials to remove contaminants [38,39].…”
Section: Introductionmentioning
confidence: 99%